Histopathological and Immunohistochemical Study of Endometrial Lesions Obtained from D&C and Hysterectomy Specimens at a Tertiary Care Hospital - Bhattacharya, Aarti B; Jha, Monalish; Agarwal, Anjana; Gupta, Vivek; Shukla, Mukesh; Kumar, Raman (Annals of Pathology and Laboratory Medicine, 2018)
Background: Endometrial lesions are represented by a set of diversified disorders which has challenged clinicians for a long time. Due to its chances of progressing to malignant states, the condition needs prompt and focussed study, keeping clinical context in view. Methods: This 12-month (June 2016-May 2017) cross-sectional study involved 100 specimens from dilatation and curettage (D & C) and hysterectomy specimens from female patients aged â‰¥ 18 years who presented with complain of pelvic pain, abnormal uterine bleeding, dysmenorrhoea, pelvic mass and infertility. For all the specimens received, histopathological and immunohistochemical assessment was done. Results: Out of 100 cases of abnormal uterine bleeding 44 females showed physiological changes, 25 females showed benign lesions and 20 females had malignant lesions of endometrium. Out of 20 cases of endometrial carcinoma 50 % were well differentiated and 25% were moderately differentiated and 25% were poorly differentiated. Expression of Ki-67 was >35% in poorly differentiated carcinoma. Well differentiated carcinoma showed 80-85% positivity of ER, moderately differentiated showed 30-35% positivity and poorly differentiated carcinoma showed 6-12%. The association between benign and malignant endometrial lesion was found to be statistically significant with age-group, history of contraceptive use and chronic illnesses (p<0.05). Conclusion: Endometrial biopsy is one of the prompt tools in diagnosis and assessment of the benign and malignant diseases of endometrium. Immunohistochemical markers like ER (hormonal receptor) and Ki-67 ( proliferative marker) play a major role in diagnosis, prognostication and therapeutic management of malignant cases.